Tsunami evacuation facility choice behavior model in flat area and rias area considering possibility to remain at home - Yoshihara, Hiroyuki; Kishimoto, Tatsuya (Collective Dynamics, 2020)
The tsunami associated with the Great East Japan Earthquake that occurred on March 11, 2011 caused enormous damage to the coast of the Pacific Ocean. Since the occurrence of the Great Earthquake, it is urgent to develop tsunami evacuation countermeasures against the great tsunamis caused by the large earthquake that is expected to occur in the future in the country and coastal municipalities. In this study, we used logit model to estimate each parameters about the relationship between evacuees and buildings in flat area and rias area by using the evacuation behavior survey data of the Great East Japan Earthquake in 2011. The estimated results show that “whether the evacuation destination is home or not” is important when people choose the tsunami evacuation destination. Moreover, by comparing the moving in flat area and in rias area the difference between them becomes clear. By using these models, it enables to estimate the home selection probability in flat area and rias area.